Public relations perspectives: Linking corporate brand and product brand to employer branding - Aruman, Akhmad Edhy; Ramonita, Latifa; Alexandrina, Elke; Utami, Puput Putri (PRofesi Humas, 2026)
Background: Mass layoffs in digital platform companies have intensified public scrutiny of employer branding, particularly within the sharing economy, where corporate reputation, social responsibility, and workforce relations are closely interconnected. In the case of PT GoTo Gojek Tokopedia Tbk., employment termination decisions have raised questions about how corporate and product brands are interpreted by prospective employees. In this context, Corporate Social Responsibility (CSR) as a part of Public Relations communication approach, emerges as a strategic communication resource that may mediate the relationship between brand reputation and employer branding. Purpose: This study examines the influence of corporate brand and product brand on employer branding and analyzes the mediating role of CSR within a sharing economy business context. Methods: This research adopts a quantitative explanatory approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Survey data were collected from 138 job seekers who were familiar with PT GoTo Gojek Tokopedia Tbk. Corporate brand and product brand were treated as exogenous variables, employer branding as the endogenous variable, and CSR as a mediating variable. Results: The findings show that corporate brand, product brand, and CSR have a positive and significant influence on employer branding. CSR demonstrates the strongest direct effect and fully mediates the relationships between corporate brand and employer branding, as well as between product brand and employer branding. Conclusion: The study indicates that employer branding in the sharing economy is not shaped solely by corporate or product reputation but is substantially strengthened through perceived CSR practices, which translate brand meaning into employer attractiveness. Implications: This research suggests the integration of CSR into corporate and product brand communication as an employer branding strategy. Academically, it contributes to public relations and employer branding literature by positioning CSR as a mediating variable in the sharing economy.